Silent Epistemology in Tahfidz Learning: The Role of Napping in Memory Consolidation - Taufikin Taufikin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
Modern education still tends to view learning as a continuous conscious activity, thereby overlooking the role of the resting phase in the cognitive process. This study aims to reconstruct the meaning of napping in tahfidz learning as a philosophical phenomenon through the perspectives of ontology, epistemology, and axiology. The study was conducted at Madrasah Ibtidaiyyah Pesantren-Based through observations of 530 students and in-depth interviews with students, teachers, and religious leaders, using a qualitative approach grounded in philosophical-contextual analysis. The results indicate that napping serves as a rhythmic structure in learning, bridging phases of activity and consolidation. Students experience improved fluency in memorization, reduced errors, and enhanced clarity of thought after napping. These findings affirm that knowledge is formed not only through conscious processes but also through latent processes operating in silence. Furthermore, this practice contributes to emotional stability, psychological balance, and a more human-centered learning experience. The primary novelty of this study lies in the formulation of the concept of “silent epistemology” as a new paradigm in tahfidz education. Its implications point toward the reconstruction of learning designs that are more aligned with students’ biological rhythms and spiritual needs.